2018
DOI: 10.7224/1537-2073.2017-002
|View full text |Cite
|
Sign up to set email alerts
|

Short Report: A Pilot Study of a Group Positive Psychology Intervention for Patients with Multiple Sclerosis

Abstract: The 5-week group positive psychology intervention was feasible and acceptable to patients with MS. A randomized controlled trial is necessary to further explore the effectiveness of the group intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The first finding of this research is the effect of the positive psychotherapeutic intervention on reducing the psychological symptoms (stress, anxiety, and depres-sion) of MS patients, which agrees with the results of authoritative research of Moghtaderi et al and Leclaire et al [24][25][26][27].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The first finding of this research is the effect of the positive psychotherapeutic intervention on reducing the psychological symptoms (stress, anxiety, and depres-sion) of MS patients, which agrees with the results of authoritative research of Moghtaderi et al and Leclaire et al [24][25][26][27].…”
Section: Discussionsupporting
confidence: 88%
“…As a theorist of positive psychology, Layous et al have directly attributed the positive interventions to the wellbeing qualities and the reduction of negative emotional reactions and also have defined positive thoughts as a cause for positive behaviors and emotions [25]. In many different studies, the effect of positive psychology-based interventions on reducing psychological symptoms has been reported to be significant [26,27]. In this regard, the studies of various researchers have shown the significant effect of positive group-psychotherapy and their components on the quality of life [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LeClaire et al 130 implemented a 5-week positive psychology programme. The results showed only a significant improvement in the SF-36 vitality subscale.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted psychological interventions based on psychoeducation and cognitive behavioral therapy may be offered to them [36, 37] to maintain a stable QoL level [38]. Interventions based on optimism or positive thinking have revealed satisfactory well-being predictors on not only the individuals themselves [3941] but also their relatives [42].…”
Section: Discussionmentioning
confidence: 99%